Risk factors associated with vestibulocochlear nerve schwannoma: systematic review Fatores de risco associados ao Schwannoma do nervo vestibular: revisão sistemática - Ana Paula Corona; Jacqueline Carneiro Oliveira; Fábia Pinheiro Andrade de Souza; Liane Viana Santana; Marco Antônio Vasconcelos Rêgo (Brazilian Journal of Otorhinolaryngology, 2009)
The vestibulocochlear nerve schwannoma (VS) is a benign tumor that stems from the edge of the Schwann´s sheath. It is considered the most frequent intracranial benign tumor, of low lethality rate and unknown etiology. AIM: to identify risk factors associated with VS. STUDY DESIGN: systematic review. METHODS: electronic search of studies using the following key words: "risk", "schwannoma", "vestibular", "neuroma" and "acoustic". All original articles on epidemiological studies published in Portuguese, English or Spanish describing measures of association were included. RESULTS: twenty case-control studies were found, most of them published in the United States. The analysis of those studies shows educational level, household income, occupation, exposure to ionizing radiation and noise, allergic diseases as well as the use of both cellular and cordless phones as risk factors for the VS. CONCLUSION: methodological limitations and lack of precision in the findings impose limits to definitive conclusions concerning those risk factors. The current study contributes with information which can subsidize decisions related to the methodology to be used, having in mind new investigations on risk factors for VS. Therefore, it is of great help for knowledge improvement in this field. O Schwannoma do nervo vestibular (SV) é um tumor benigno que se origina da bainha de Schwann do VIII par craniano. É o tumor benigno intracraniano mais frequente, de baixa letalidade e etiologia obscura. OBJETIVO: Identificar fatores de risco associados ao SV. DESENHO DO ESTUDO: Revisão sistemática. MATERIAL E MÉTODO: Identificação de estudos em bases de dados eletrônicos utilizando as palavras-chaves "risk", "risco", "schwannoma", "vestibular", "neuroma" e "acoustic". Incluíram-se artigos originais de pesquisa epidemiológica publicados em português, espanhol ou inglês, que referiam alguma medida de associação. Foram comparados e analisados aspectos metodológicos e resultados dos estudos. RESULTADOS: Foram localizados 20 estudos do tipo caso-controle, sendo a maioria publicada nos Estados Unidos. A análise dos estudos revela como fatores de risco para o SV o nível educacional, renda familiar, ocupação, exposição à radiação ionizante e ao ruído, doença alérgica e uso de telefone celular e fixo sem fio. CONCLUSÕES: Limitações metodológicas e imprecisão dos achados impõem limites a conclusões definitivas sobre os fatores de risco associados ao SV. O presente estudo contribui com informações que podem subsidiar decisões metodológicas para novas investigações sobre fatores de risco para SV e, assim, colabora para o avanço do conhecimento na área.